Creativity, challenge and culture in the languages classroom: a response to the Ofsted Curriculum Research Review. Issue 2 (4th March 2022) - Porter, Alison; Graham, Suzanne; Myles, Florence; Holmes, Bernardette
ABSTRACT: In this opinion piece we problematise foreign language (FL) learning curricula which are rigidly based on carefully sequenced input and constrained learning opportunities. Whilst an important component in language learning, language knowledge constitutes more than phonics vocabulary and grammar. Our stance is premised on the understanding that, whether novice or expert, an FL learner is not a 'tabula rasa'. In other words, every learner will have existing linguistic, social and cultural knowledge and skills, as well as cognitive and developing metacognitive resources which have the potential to both support and frustrate the language learning process. This, in turn, problematises a structured approach to teaching and learning which rests on carefully sequenced input, constrained learning opportunities and minimal exposure to unfamiliar language. We propose that FL curricula should be centred around opportunities to actively communicate in the language, supported by rich and plentiful input. We suggest that, to foster emotional engagement and intrinsic motivation, young FL learners should engage with cultural artefacts and authentic content in the target language. In addition, learning activities which offer both challenge and enough scaffolding to experience success are likely to support self-efficacy which is linked to motivation.